Thrombolytic Therapy in Haemolytic-Uraemic Syndrome - Stuart, J. (1974)
The treatment of five children with the haemolytic-uraemic syndrome using streptokinase is described to illustrate the difficulties and limitations of thrombolytic therapy in this disease. This experience is germane to the design of multicentre clinical trials. A multivariate analysis relating clinical outcome to the data obtained at the time of admission was also carried out for 31 children with the disease treated in four centres. The results suggest that this technique may help to identify those patients likely to have a fatal outcome. An expanded form of this type of analysis should be incorporated in future clinical trials.